OVERVIEW OF THE COPING MECHANISM OF NURSES IN HANDLING PATIENTS CONFIRMED POSITIVE FOR COVID-19 AT WALUYO JATI KRAKSAAN HOSPITAL PROBOLINGGO - Ilzam Suji Ajikumoro; Erti Ikhtiarini Dewi; Fitrio Deviantony (Jurnal Keperawatan Respati Yogyakarta, 2023)
During the COVID-19 pandemic, given that nurses are on the front line, maintaining mental health in this COVID-19 pandemic situation can be difficult in terms of anxiety, reducing the risk of depression or burnout. This research is essential to study. They can find out the problems experienced by nurses in dealing with Covid-19 patients and add a form of vigilance in the event of a pandemic again because the virus always mutates. This research includes several indicators, namely problem focus coping, and emotion focus coping. This study aims to describe the coping mechanisms of nurses in handling patients confirmed positive for COVID-19 at the General Hospital. This type of research is descriptive quantitative analytic using a total sampling technique with the sample population in this study being 56 nurses. This study uses zoom media and googles forms with a questionnaire on Coping Mechanisms for Nurses in Handling Covid-19 Patients from Liliek & Hery, (2021). The results obtained from the analysis of the description of the coping mechanisms of nurses in handling patients confirmed positive for COVID-19 mostly have the categories of adaptive coping mechanisms (64%), and maladaptive (36%). This shows that the nurse's coping mechanism in handling patients confirmed positive for COVID-19 is still not optimal, because nurses are not fully categorized into adaptive coping mechanisms. For health agencies, it is necessary to carry out routine activities that physically can support nurses and other health workers, namely counseling and physical activities such as sports, refreshing, relaxing, and spiritual techniques.